1992
DOI: 10.2170/jjphysiol.42.805
|View full text |Cite
|
Sign up to set email alerts
|

Heat Production Associated with a Propagated Impulse in Bullfrog Myelinated Nerve Fibers.

Abstract: By using heat-sensors constructed with thin film of polyvinylidene fluoride, it was found possible to detect the heat generated by myelinated fibers in the bullfrog sciatic nerve in association with a propagated impulse. The quantity of heat generated (about 0.4 microcal/g at 4.5 degrees C) is roughly two orders of magnitude smaller than that observed in nerves containing only non-myelinated nerve fibers. The smallness of the heat observed is attributed to the localization of the heat sources at the nodes of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 0 publications
0
46
0
1
Order By: Relevance
“…of localized pulses, exists. This model automatically addresses the observed changes in length [6] and [14] and thickness [32,16,33,34,14,35] and the reversible heat production [10,11,13,14,36].…”
Section: Discussionmentioning
confidence: 99%
“…of localized pulses, exists. This model automatically addresses the observed changes in length [6] and [14] and thickness [32,16,33,34,14,35] and the reversible heat production [10,11,13,14,36].…”
Section: Discussionmentioning
confidence: 99%
“…Further, it is clearly inconsistent with the thermal response. The initial heat release and subsequent re-absorption studied by a number of authors [16,17,18,19,20] points rather to a reversible physical phenomenon that conserves entropy. In contrast, the Hodgkin-Huxley model is based on the flux of currents through resistors that should heat the membrane independent of the nature of the current and its direction.…”
Section: Discussionmentioning
confidence: 99%
“…Further, during the action potential lipid membrane markers change their fluorescence intensity and their anisotropy [14,15]. Most striking, however, is the finding that there are reversible changes in temperature and heat during the action potential [16,17,18,19,20]. While the Hodgkin-Huxley model [6] contains resistors that should generate heat during the flow of ions, the reversible release and re-absorption of heat does not find a satisfactory explanation within this model [21].…”
Section: Introductionmentioning
confidence: 99%
“…the same direction did not result in the annihilation of the action potentials predicted by the HH model, but presented a phenomenon of mutual penetration (Heimburg and Jackson, 2014). Other studies have observed that there is no heat dissipation in the process of action potential transmission, which is an adiabatic (non-dissipative) phenomenon (Abbott et al, 1958;Howarth et al, 1968;Howarth, 1975;Ritchie and Keynes, 1985;Tasaki and Byrne, 1992). However, according to HH model, ion flow through resistance (channel protein) can lead to irreversible heat dissipation of membrane (Heimburg and Jackson, 2007), which is in contradiction with the observed results.…”
Section: Introductionmentioning
confidence: 64%